MSMEs in Surabaya: A Digitalization Literacy For Business - Ida Aju Brahma Ratih; Mulyanto Nugroho; Slamet Riyadi; Mohammad Sihab Ridwan (Pusat Riset dan Inovasi Nasional, 2023)
The ability of MSMEs to implement digital concepts in their business is becoming increasingly crucial, since changes in buying and selling transaction techniques, lifestyle changes, and developments over time all contribute to the digitalization of MSMEs. Although the majority of MSMEs in Gayungan District, Surabaya City, still employ traditional business practices, the sub-district has a lot of potential for MSMEs and has a number of frequent clients. In this exercise, information is shared through conversation, Q&A sessions, and hands-on practice with digital business software. Digital marketing through the use of marketplaces and online services through applications or websites is the method of business digitalization that is employed. Participants in this activity will be able to employ digital applications, like online marketplaces and services, in their business operations and comprehend their advantages.